Large-Scale Chromatography for the Isolation of 7S Globulin Enriched Fraction from Pigeon Pea Seeds - Locali-Pereira, Adilson Roberto [UNESP]; Solé-Jamault, Véronique; Davy, Joëlle; Cherkaoui, Mehdi; Rogniaux, Hélène; Mameri, Hamza; Le Gall, Sophie; Beaumal, Valérie; Rabesona, Hanitra; Laurent, Sophie; Nicoletti, Vânia Regina [UNESP]; Berton-Carabin, Claire; et al. (American Chemical Society (ACS), 2025)
Pigeon pea (Cajanus cajan) contains around 60% globulin proteins, of which 7S globulin is the most abundant fraction. In this work, a purification protocol for pigeon pea 7S globulin was developed using large-scale chromatography. The process was designed on an analytical scale through desalting of the crude protein extract followed by anion exchange chromatography and size exclusion chromatography. Then, the process was scaled up to a large scale. The purified fraction presented a protein content of 89 g/100 g powder and yield close to 23%. The isolated 7S globulin showed two main subunits of 64 and 49 kDa, identified as the α- and β-chains of β-conglycinin by proteomic analysis. The developed protocol was shown to be suitable for purifying pigeon pea 7S globulin on a large scale, and it is relevant for isolating this fraction from other pulse seeds in sufficient quantities for their characterization and evaluation of functional properties.